Descriptive study of workplace demand, control and bullying among migrant and Australian-born workers by gender: does workplace support make a difference?. Issue 6 (28th June 2020) - Reid, Alison; Daly, Alison; LaMontagne, Anthony D; Milner, Allison; Ronda Pérez, Elena
Abstract : Objective: The objective of this study is to examine the relationship between bullying in migrants and Australians and types of workplace Iso-strain, by gender. Design and setting: Two descriptive cross-sectional surveys of the Australian working population. Participants: Australian-born workers of Caucasian ancestry (n=1051, participant response rate=87.3%) and workers born in New Zealand (n=566), India (n=633) and the Philippines (n=431) (participant response rate=79.5%). Primary and secondary outcomes measures: Using logistic regression, we examined whether self-reported assessment of various forms of bullying in the workplace was associated with Iso-strain (job with high demands and low control and without social support), gender and migrant status. Results: The prevalence of workplace bullying within the previous year was 14.5%. Sexual harassment, though rare (n=47, 1.8%), was reported by more women than men (83% vs 17%, χ 2 =19.3, p<0.0001) and more Australia or New Zealand born workers compared to India or the Philippines workers (75.5% vs 25.5%, χ 2 =4.6, p=0.032). Indian-born women had lower adjusted OR for being bullied and for being intimidated compared to other women. Independent of migrant status, Iso-strain (1), (low support from boss) and Iso-strain (2), (low support from colleagues) predicted being bullied. Women were more likely to be in an Iso-strain (1) job than men (18.7% vs 13.6%, p=0.013) and had twice the risk of being both verbally abused and intimidated compared to men (OR 9 vs OR 5.5, p<0.0001). Conclusion: Workplace bullying was more likely for women than men. There were few differences between workers from different migrant groups. Iso-strain was the strongest predictor of workplace bullying. Workplaces should encourage supportive and collegiate work environments.